A inteligência artificial no processo de integração da União Europeia - Alves, Kethelin Wisnieski Barretto (Universidade do Vale do Rio dos Sinos, 2022)
In recent years, the increase in available data and the greater processing capacity of computers has led to an evolution of artificial intelligence. This technology, as one of the key technologies of the Fourth Industrial Revolution, is increasingly present in our lives and is transforming the world. It is not yet known what impacts the development and use of artificial intelligence will have in the world and therefore there is an increasing amount of research on the subject. Even so, there are relatively few researches that deal with the subject in the area of International Relations, therefore, this monograph seeks to bring greater contributions to the area of International Relations. The general objective of this work, therefore, is to understand the configuration of Artificial Intelligence in the European Union, since the bloc is one of the most relevant geographic regions on the subject, due to its approach, which seeks to collectively respond to the challenges generated by Artificial Intelligence while guides its development and use for the benefit of its member states. As for the methodology used, this study is an exploratory research with a qualitative approach, as it is a relatively new topic with few studies. Through this study it is understood that artificial intelligence is a challenge for the European Union, but mainly an opportunity. The bloc is gaining advantages by guiding the development and use of artificial intelligence and becoming a world reference on the subject, showing the importance of policies that guide the development of this technology.
Keywords: Inteligência artificial; Teoria da interdependência complexa; Integração; União Europeia; Artificial intelligence; Theory of complex interdependence; Integration; European Union